Analisis Strategi Budaya Perusahaan untuk Meningkatkan Sumber Daya Manusia di CV Rumah Mesin Yogyakarta - Nabilah Qurrotu Ain; Husna Fitria Arifatunnisa; Anthonio Adhi Setiawan; Henida Putri Salsabila; Aldi Dwi Saputra (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze corporate culture strategies in enhancing reliable and morally upright human resources at CV Rumah Mesin Yogyakarta. The research will examine the moral values applied at CV Rumah Mesin Yogyakarta and their impact on employee performance and quality. This study uses a qualitative case study method at CV Rumah Mesin Yogyakarta. Data is collected through in-depth interviews, observations, and documentation. The results of this study indicate that corporate culture strategies can improve reliable and morally upright human resources. The corporate culture at CV Rumah Mesin Yogyakarta includes spirituality, solidarity, ethics, and a performance development system as key factors to enhance human resource competence. Based on interviews and observations, CV Rumah Mesin Yogyakarta places great emphasis on the quality of its human resources by providing continuous training and solidarity programs, such as Qur’an recitation, office cleaning, and sports activities for all employees. The findings of this study are expected to contribute to the literature on human resource management and provide strategic guidance for service companies to increase their competitiveness through effective human resource development.